ORAL PAPILLARY SQUAMOUS CELL CARCINOMA: CASE REPORT AND LITERATURE REVIEW - Lísia Daltro Borges Alves; Alessandra Laís Pinho Valente Pires; Tarsila de Carvalho Freitas Ramos; Márcio Campos Oliveira; Valéria Souza Freitas (Portal de Periódicos da Marinha do Brasil, 2021)
Papillary squamous cell carcinoma is a tumor that affects the upper aerodigestive tract, but rarely the oral cavity. The aim of this study is to report a case of oral papillary squamous cell carcinoma and to review the available literature. We present a case of a 73-year-old man patient with two intraoral lesions with three-month evolution. An ulcerated exophytic lesion measuring 1.5 cm was detected in the left alveolar ridge region/mouth floor and an ulcerated lesion in the left retromolar region measuring 1 cm. Moreover, we identified a symptomatic hardened lymph node on the level 1B of the left side, measuring 4×3 cm. Both intraoral lesions were biopsied and the one in the alveolar ridge/mouth floor was diagnosed as papillary squamous cell carcinoma - composed of atypical cells, basaloids and in papillary disposition. At the time of staging, the tumor had 4×6 cm being staged as T3N2aM0 (IV-A) and the employed treatment was chemotherapy associated with radiotherapy. After two years of follow-up, the patient is alive and without evidence of the disease, lymph node or distant metastases. Therefore, the papillary squamous cell carcinoma is a rare tumor in the oral cavity with few reported cases. This case report emphasizes the importance of histopathological examination for the accurate diagnosis and its role in determining appropriate treatments and prognosis.